Ethyl 3-Ethoxy-3-iminopropanoate Hydrochloride: A Versatile Precursor for Generating Next-Generation Energetic Materials - Kukreja, Sonali; Dharavath, Srinivas (Synthesis, 2025)
The construction of nitrogen-rich heterocycles is a cornerstone in developing high-energy-density materials (HEDMs). Ethyl 3-ethoxy-3-iminopropanoate hydrochloride (EEIP·HCl) has proven to be a particularly powerful precursor, offering a reliable and versatile route to make several nitrogen-rich frameworks. Its ability to streamline ring formation has enabled the synthesis of high-performing energetic compounds with desirable densities, stabilities, and detonation properties. This article reviews EEIP-mediated cyclizations in energetic materials, underscoring its exceptional synthetic utility, broad structural scope, and growing role in advancing next-generation, environmentally sustainable explosives.
Keywords: Ethyl 3-ethoxy-3-iminopropanoate; Polynitro compounds; Triazoles; Oxadiazole; Energetic materials